Implementasi Pendidikan Agama Islam Berbasis Pendekatan Open-Ended Dalam Meningkatkan Akhlak Peserta Didik di SDIT Daar Ilmi dan SD N 1 Lembasung Kecamatan Blambangan Umpu Kabupaten Waykanan Tahun Pelajaran 2022/2023 - Lestiani, Famelia; Setyaningsih, Rina; Ekowati, Endang (Jurnal Pendidikan Rafflesia, 2023)
This research was conducted at SDIT Daar Ilmi and SD N 1 Lembasung Waykanan district with problems about the implementation of Islamic religious education based on an open ended approach, namely preparation, implementation, and evaluation. The formulation of the problem in this study is: 1) How is the Implementation Process of Islamic Religious Education Based on an Open-Ended Approach in Improving the Morals of Students at SDIT Daar Ilmi and SD N 1 Lembasung, Blambangan Umpu District, Waykanan Regency for the 2022/2023 Academic Year? 2) What factors hinder the implementation of open-ended approach-based Islamic religious education in improving the morals of students at SDIT Daar Ilmi and SD N 1 Lembasung, Blambangan Umpu District, Waykanan Regency for the 2022/2023 academic year? 3) What factors support the implementation of Islamic religious education based on an open-ended approach in improving the morals of students at SDIT Daar Ilmi and SD N 1 Lembasung, Blambangan Umpu District, Waykanan Regency for the 2022/2023 academic year? The purpose of this study is to find out why the implementation of the Open-Ended Approach in SMA Negeri 1 Blambangan Umpu. The Open-Ended approach is a very effective approach when implemented in the learning process. The implementation of the Open-Ended Approach, makes students able to think creatively and solve problems and can express opinions in the learning process in class. This research uses descriptive qualitative research, this type of research uses case studies and data collection processes, namely interview methods, observation methods, and documentation methods. Data analysis techniques use data collection, data reduction, data presentation, and verification. The results of this pre-study show that the Implementation of Islamic Religious Education Based on an Open-Ended Approach in Improving the Morals of Students at SDIT Daar Ilmi and SD N 1 Lembasung, Blambangan Umpu District, Waykanan Regency shows that the steps of the Open-Ended Approach include 3 steps. However, there is still one step in the approach that has not been maximized, namely in the core activity step, the teacher has not used the discussion method so that students are passive and lack the response or enthusiasm of students in the process of learning activities in class. However, after the steps were implemented optimally, the results of the study showed that students experienced a good and satisfying moral improvement. This can be seen from the psychomotor aspect (skills) of daring to present and demonstrate, students become enthusiastic and enthusiastic in following learning, in the process of classroom learning becomes alive. The affective aspect (attitude) can be said to be the maximum of the morals of speaking, the morals of attitude, and the morals of behavior. The cognitive aspect (knowledge) of learners has improved in terms of their comprehension and daily tests.